2000
DOI: 10.1046/j.1523-1755.2000.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation and lipidoxidation of the peritoneal membrane: Respective roles of serum and peritoneal fluid reactive carbonyl compounds

Abstract: Protein modification of the peritoneum is determined not only by RCOs originating in PD fluid, but also by RCOs originating from the uremic circulation. The present data might be relevant to current attempts to improve PD fluid toxicity by lowering its glucose content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
95
2
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 31 publications
9
95
2
3
Order By: Relevance
“…In this study, we demonstrate that neither olmesartan, an AIIR antagonist, nor temocaprilat, an ACE inhibitor, entrap and lower in vitro the concentration of two RCO, glyoxal and methylglyoxal. This finding stands in contrast with aminoguanidine and OPB-9195, both of which, at equimolar concentrations, markedly reduce the levels of both RCO, confirming previous observations (28). Pyridoxamine has an intermediary effect.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, we demonstrate that neither olmesartan, an AIIR antagonist, nor temocaprilat, an ACE inhibitor, entrap and lower in vitro the concentration of two RCO, glyoxal and methylglyoxal. This finding stands in contrast with aminoguanidine and OPB-9195, both of which, at equimolar concentrations, markedly reduce the levels of both RCO, confirming previous observations (28). Pyridoxamine has an intermediary effect.…”
Section: Discussionsupporting
confidence: 90%
“…At the end of the incubation period, two major arabinose degradation products, glyoxal and methylglyoxal, for which pure standards are available, were identified and quantitated by HPLC (28). The standards were used for calibration purposes.…”
Section: Inhibition Of Dicarbonyl Formation By Olmesartanmentioning
confidence: 99%
“…Several in vitro studies have suggested that the presence of several aldehydes and 1,2-dicarbonyl compounds is partly responsible for the cytotoxicity of these fluids [8,9]; however, we have previously demonstrated a minor effect of GDPs on morphological/cellular alterations of the peritoneum in vivo [4]. GDPs can also promote the irreversible formation of advanced glycation end products (AGEs), which in turn can potentially contribute to the toxicity of PD fluids [10]. There is considerable evidence suggesting cytotoxic effects of lactate as the common buffer used in the conventional PD fluids [11].…”
Section: Introductionmentioning
confidence: 81%
“…A growing body of evidence indicates increased concentration of malondialdehyde, a byproduct of the peroxidation of polyunsaturated fatty acids, in plasma and erythrocytes of CPD patients (11,21,22). It has also been shown that plasma levels of advanced glycation end products and advanced oxidation products of proteins are increased in CPD patients compared with healthy subjects (23,24). In contrast to lipids, sugars, and proteins, the reactions of DNA with various oxidants have not been well studied in CPD patients.…”
mentioning
confidence: 99%